Neighbourhood deprivation across eight decades and late-life cognitive function in the Lothian Birth Cohort 1936: a life-course study. (23rd April 2023) - Baranyi, Gergő; Conte, Federica; Deary, Ian J; Shortt, Niamh; Thompson, Catharine Ward; Cox, Simon R; Pearce, Jamie
Abstract: Introduction: although neighbourhood may predict late-life cognitive function, studies mostly rely on measurements at a single time point, with few investigations applying a life-course approach. Furthermore, it is unclear whether the associations between neighbourhood and cognitive test scores relate to specific cognitive domains or general ability. This study explored how neighbourhood deprivation across eight decades contributed to late-life cognitive function. Methods: data were drawn from the Lothian Birth Cohort 1936 ( n  = 1, 091) with cognitive function measured through 10 tests at ages 70, 73, 76, 79 and 82. Participants' residential history was gathered with 'lifegrid' questionnaires and linked to neighbourhood deprivation in childhood, young adulthood and mid-to-late adulthood. Associations were tested with latent growth curve models for levels and slopes of general ( g ) and domain-specific abilities (visuospatial ability, memory and processing speed), and life-course associations were explored with path analysis. Results: higher mid-to-late adulthood neighbourhood deprivation was associated with lower age 70 levels ( β  = −0.113, 95% confidence intervals [CI]: −0.205, −0.021) and faster decline of g over 12 years ( β  = −0.160, 95%CI: −0.290, −0.031). Initially apparent findings with domain-specific cognitive functions (e.g. processing speed) were due to their shared variance with g . Path analyses suggested that childhood neighbourhood disadvantage is indirectly linked to late-life cognitive function through lower education and selective residential mobility. Conclusions: to our knowledge, we provide the most comprehensive assessment of the life-course neighbourhood deprivation and cognitive ageing relationship. Living in advantaged areas in mid-to-late adulthood may directly contribute to better cognitive function and slower decline, whereas an advantaged childhood neighbourhood likely affects functioning through cognitive reserves.